Evaluating Inflorescence Morphology in Two Species and Subspecies of the Genus Hierochloë R. Brown - Károly Penksza; Tünde Szabó-Szöllösi; András Neményi; László Sipos; Szilárd Szentes; Zsombor Wagenhoffer; Balázs Palla; Dániel Ákos Balogh; Eszter Saláta-Falusi (Plants)
(1) The primary objective was to determine whether, within this taxonomically challenging group, the closely related European species and their subspecies exhibit distinct inflorescence characters that allow for unambiguous differentiation. This study focuses on two closely related species within the genus Hierochloë: Hierochloë hirta (Schrank) Borbás and Hierochloë odorata (L.) Beauv. (2) For four subspecies, data were collected from 15 inflorescences each, while for one subspecies, 10 inflorescences were examined. From each inflorescence, six spikelets were selected. The statistical analyses were non-parametric methods, the Kruskal–Wallis test, and principal component analysis. (3) Morphological traits showed consistent patterns within each subspecies, indicating their suitability for taxonomic differentiation. The most reliable diagnostic traits were the length of the outer glume of the first flower and the lengths of the awns. (4) The study concludes that while some subspecies can be clearly distinguished based on inflorescence morphology, no single trait is sufficient to completely separate all taxa. The authors recommend recognizing Hierochloë odorata subsp. praetermissa as a subspecies rather than a distinct species and affirm the validity of the species names Hierochloë hirta and Hierochloë odorata.